Factors Influencing The Financial Independence of Young Adults, an Evidence from Indonesia - Evelyn Evelyn; Ricky Ricky; Sherly Rosalina Tanoto (Master of Management, School of Business and Management, Petra Christian University, 2021)
Financial independence is a mark of an individual’s maturity. Achieving financial independence for an individual is very important for family life. Society would be better off when most of its members were independent financially. This study investigates whether different groups of young adults based on their age, gender, education, and income significantly differ in their financial independence. Also, this research intends to study demographic factors that influence the financial independence of a society. The research method was quantitative by using a survey with 539 respondents. The result shows that different groups of young adults categorized based on age, gender, education, and income have a significant difference related to financial independence. Age and income are the two most important factors influencing the financial independence of young adults.